Framing Multifunctionality: Agricultural Policy Paradigm Change in South Korea and Japan? - Sakamoto, Kiyohiko; Choi, Yong-ju; L. Burmeister, Larry (The International Journal of Sociology of Agriculture and Food, 2007)
In response to domestic sectoral adjustment and WTO regime pressures, policymakers in South Korea and Japan are proposing multifunctionality agricultural policy alternatives to traditional agricultural subsidy policies. Using discourse analysis of recent South Korean and Japanese agricultural policy documents to identify policy frames, significant differences are found in the two countries’ multifunctionality policy initiatives in terms of rural/agriculture sector development goals, present versus future orientation, and the scope of agri-food system applications. These differences are linked to variations in economic structure, political-institutional policymaking frameworks, and societal trajectory visions that currently characterize the agricultural/rural policymaking environment in the two countries.